Mellon Collie and the Infinite Sadness. Metamorfosis de la melancolía en tres poetas españoles del nuevo milenio (TEST Ticontre. Theory Text Translation, 2018)
The album’s title Mellon Collie and the Infinite Sadness (1995) by the American band The Smashing Pumpkins, which marked a whole generation of Spanish youths, is used here as leitmotiv to look for the ways in which melancholy, this aptitude which since the Renaissance, as analyzed by Fritz Saxl and Erwin Panofsky was related to the genius, is dealed with by three Spanish poets of the XXI century. Taking into account the theories of politic (Traverso) and love melancholy (Barthes) as well as other melancholy views (from Kristeva to Han) this paper attemps to deal the treatment wich in the poetics of Julio César Galán, Juan Andrés García Román and Pablo López Carballo, the melancholy can be related to lost ideals, physical and spiritual distance of the beloved or the lack of references in contemporary life.El título del disco Mellon Collie and the Infinite Sadness (1995) de la banda norteamericana The Smashing Pumpkins, que marcó a una generación de jóvenes españoles, nos sirve como hilo conductor para indagar en las formas en las que la melancolía, que como analizaran Fritz Saxl y Erwin Panofsky, a partir del Renacimiento fue adquiriendo un carácter positivo relacionado con el genio poético, aparece en tres poetas españoles cuya obra se inscribe en el nuevo milenio. Teniendo en cuenta el análisis de las melancolías política (Traverso) y amorosa (Barthes) así como otras perspectivas sobre la melancolía (de Kristeva a Han), analizamos cómo en Julio César Galán, Juan Andrés García Román y Pablo López Carballo esta melancolía puede relacionarse con los ideales perdidos, la lejanía (física o espiritual) de la amada o la falta de referentes en el mundo contemporáneo.